MetCirc: navigating mass spectral similarity in high-resolution MS/MS metabolomics data - Naake, Thomas; Gaquerel, Emmanuel (Bioinformatics, 2017)
AbstractSummary. Among the main challenges in metabolomics are the rapid dereplication of previously characterized metabolites across a range of biological sam
Gesehen am 30.08.2018